As políticas educacionais implementadas pelo município de Belterra/PA no período de 1997-2012 - SANTOS, Ângela Rocha dos (Universidade Federal do Oeste do Pará, 2021)
This research addresses the issue of educational policies in municipal scope, aiming to identify and record the educational policies implemented by Belterra Department of Education, in the state of Pará, in the period of 1997-2012, considering the Brazilian education legal and historical landmarks. Such as the Law on Brazilian Education Guidelines and Bases, Public Law 9.394 (Dec. 20, 1996), the educational reforms that took place from the 1990s, which enable the historical record of the municipal education improvement policies. As theoretical support, among other authors, we are using Azevedo (2001), Saviani (2001), and Oliveira (2011) that address education as a social public policy, and school education a right for all and duty of the State. Qualitative research was our methodology, with the following analysis categories: decentralization and autonomy; programs and projects developed by the Department. To obtain data we used as techniques and research tools: documental analysis (primary and secondary sources) and semi-structured interviews with the secretaries of Municipal Education Department from the delimited study period. The results showed that the Department has articulated and developed actions, programs and projects from federal, state and private initiative accession, which allowed both institutional learning and practices for decentralization and autonomy in search for administrative, financial and educational improvement of the municipal education organization. At the macro level, the rise of educational programs to materialization of educational policies inducing actions. Due to the fragility of municipal structure as a federal entity, for it is an eminently rural municipality and territorial coverage domain of the government, 90% of environmental protected area, interferences in the educational field in the policies created by the Department of Education were observed. The lack of municipal education plan and system, and documental records was identified, which allowed us to observe the shortage in carrying out collective work as guidelines, goals, and planned and systematized actions in short, medium and long term, permanently, by the Department, so that there could be follow-up, monitoring and evaluation of actions and policies over the period.